Financial report preparation training to increase human resource capacity at BUMDes Tamantirto Kasihan Bantul - Nano Prawoto; Ilham Maulana Saud; Adhianty Nurjanah (Community Empowerment, 2023)
This community service program is motivated by empirical facts that the management and preparation of financial reports are not in accordance with standard accounting financial reporting standards at BUMDes Taman Karya Menunggal Tamantirto, Kasihan, Bantul. There is a need to increase the capacity of human resources (HR) in BUMDes, especially in financial management capabilities. The purpose of this activity is to increase HR capacity in terms of financial reporting and company services owned by Tamantirto Village. The methods used were (1) focus group discussions with BUMDes Taman Karya Manunggal, (2) Training on making BUMDes financial reports, and (3) providing tools for preparing financial reports. The result of this activity was an increase in participants' understanding of 80% regarding the importance of BUMDes financial management and financial reports. In addition, there is also an 85% increase in knowledge of making a financial management system.